Ceramides in Adipose Tissue - Li, Ying; Talbot, Chad Lamar; Chaurasia, Bhagirath (Frontiers in Endocrinology, 2020)
Adipose tissue is a key nutrient-sensing depot that regulates excess energy storage and consumption. Adipocytes, the key components of the adipose tissue, have unique ability to store excess energy in the form of triglycerides, sense systemic energy demands, and secrete factors (lipids, peptides, cytokines, and adipokines) to regulate other metabolic tissues. The presence of various types of adipocytes (white, brown, and beige) characterized by the number/size of lipid droplets, mitochondrial density, and thermogenic capacity, further highlights how intricate is the communication of these cell-types with other metabolic tissues to sense nutrients. In obesity the inherent capacity of adipose tissue to store and sense nutrients is compromised, causing spillover of the intermediate lipid metabolites into circulation and resulting in their ectopic deposition in tissues not suitable for lipid storage, a phenomenon known as lipotoxicity. This results in a spectrum of cellular dysfunction, that underlies various metabolic diseases. Of the numerous lipid classes implicated in eliciting lipotoxicity, sphingolipid: ceramides are among the most deleterious as they modulate signaling pathways involved in regulating glucose metabolism, triglyceride synthesis, apoptosis, and fibrosis. Notably, recent experimental studies have strongly implicated ceramides in the development of numerous metabolic diseases such as insulin resistance, diabetes, cardiomyopathy, hepatic-steatosis, and atherosclerosis. Herein we discuss and summarizes recent findings that implicate ceramides as a key contributor to adipocyte dysfunction underlying metabolic diseases and how depletion of ceramides can be exploited to improve metabolic health.